The Effectiveness of the Technique of Counseling with a Lecture about the Protocols of Health Knowledge, Attitude and Behavior of the Community in the Pandemic of Covid-19 in Puskesmas Sei Suka - Melysa Melysa; Chrismis Novalinda Ginting; Sri Wahyuni Nasution; Ermi Girsang (Budapest International Research and Critics University, 2022)
Corona Virus Disease 19 or better known as the corona virus or Covid-19 is an emergency global health. To reduce and prevent transmission of this virus, the government has required people to keep the protocol health but people still do not comply. This study aims to determine the effectiveness of the technique of counseling with a lecture about the protocols of health knowledge, attitude and behavior of the community. The type of this research is experimental (experimental), namely quasi-experimental (quasi-experimental) design with pretest and posttest. The sample in this research is that people in the working area of Puskesmas Sei Suka as many as 100 people. Data were analyzed using Paired T-test. The results of the research that there is influence between the extension teaching methods of the protocols of health knowledge (p=0,021), attitude (p=0.008) and behavior (p=0.016). It is recommended to the relevant government agencies in the District of Coal to be intense counseling to the community, especially about the protocol health a daily habit; do the inspection if the condition of the body is not healthy.